Management Accounting Strategy in Decision Making to Achieve Good Governance - Pasaribu, Hiras; Lidyawati, Linda; Sihombing, Edison; Majid, Jamaluddin (Dhana, 2025)
This study aims to explore the contribution of management accounting strategies in supporting rational and accountable decision-making in order to realize the principles of good governance. Through the Systematic Literature Review (SLR) approach, this study systematically and comprehensively examines various relevant scientific literature, in order to identify strategies, patterns, and relationships between management accounting and good governance practices. The SLR process was carried out following the PRISMA flow, including formulating research questions, determining inclusion and exclusion criteria, and screening articles from reputable scientific databases such as Scopus, Google Scholar, ScienceDirect, ProQuest, and Garuda. The results of the study indicate that management accounting strategies, through tools such as budgeting, variance analysis, and cost-benefit analysis, play an important role in creating an efficient, data-based, and documented decision-making system. In addition, the use of information technology such as ERP, e-budgeting, and e-performance strengthens data integration, accelerates reporting, and increases transparency and accountability. This study also emphasizes the importance of increasing human resource capacity and internal policies that support the optimal use of accounting information. Thus, management accounting strategy is not only a technical tool, but also a strategic foundation in building professional, transparent and sustainable organizational governance